Edutainment as an effective education technology - Koval, Olha; Коваль, Ольга Юріївна; Коваль, Ольга Юрьевна (Марусич, 2020)
Development and optimization of new technologies and training techniques aimed at training of the competent specialist, capable of effectively solving the practicefocused problems that require the abilities of foreign-language oral speech communication, is the main objective of higher education within the competence-based approach.
Keywords: high school teacher; students; learning technologies; extracurricular classes